Paternal Age and its Relation with Congenital Cardiac Defects in Down’s Syndrome at Children Hospital & ICH, Lahore - Areiba Haider, Sarah Khan, Sania Asif, Raafea Tafweez (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of Subtypes of Down’s syndrome and congenital cardiac defects in Down’s syndrome population and its association with parental age at Children Hospital, Lahore. Study Design: Cross sectional study Duration of Study: June 2016 to June 2017 at Genetics Deptt. Children Hospital, Lahore Methodology: A total of 160 patients were included after taking an informed consent. A detailed history and physical examination for Down’s syndrome was done. All the cases underwent karyotypic analysis for determination of the subtype of DS and echocardiography of all cases was done for CHD. Data was analyzed by SPSS 21. Results: Mostly mothers i.e. 56(35%) were in the age of 26–30 years and fathers 99 (69.1%) in age of 31–40 years when they conceived a Down’s syndrome baby. On karyotyping, the frequency of Trisomy 21 was highest in mothers in age group 02 and fathers in age group 03. PDA and VSD were common cardiac defects in Down’s syndrome cases. In mothers, mostly PDA and VSD was present in age group 02 and fathers in age group 03. Conclusion: Common type of Down’s syndrome was Trisomy 21. Most common CHD were PDA and VSD. Most of the Down’s syndrome babies were born to mothers in age group 25 to 30 years and fathers in age group 31 to 40 years.